Best Answer

Related Post

Spread the word

Digg this post

Bookmark to delicious

Stumble the post

Add to your technorati favourite

Subscribes to this post

2 Comments Already

mygif
? ? ? ? Said,
January 24th, 2011 @5:06 am  

x(x+0.01)/(0.01-x) = 0.12

Expand numerator and multiply both sides of equation by (0.01-x):

x² + 0.01x = 0.0012 – 0.12x
x² + 0.13x – 0.0012 = 0

Now you can use the formula.

mygif
Julia Said,
January 24th, 2011 @6:04 am  

(0.01x + x^2) / (0.01 – x) = 0

multiply the fraction by (0.01 – x) and the 0 by (0.01 – x) [to get rid of the denominator]

hence
(0.01x + x^2) = 0

or

x^2 + 0.01x = 0

now you can use the quadratic formula (where b = 0.01 , a = 1, and c = 0)

hope i helped!!

Leave Your Comments Below

Please Note: All comments will be hand modified by our authors so any unsuitable comments will be removed and you comments will be appreared after approved